Dysfunction of the meibomian glands in patients with diabetes mellitus - T. N. Safonova; E. S. Medvedeva (Сахарный диабет, 2022)
The prevalence of diabetes mellitus has increased in recent decades. The most common ophthalmic manifestations of diabetes mellitus are retinopathy, epitheliopathies, corneal erosion and dry eye syndrome, the symptoms of which are more pronounced than in people without diabetes. The meibomian glands, which are the producer of various lipids, participate in the formation of the lipid layer of the tear film, which prevents the evaporation of the water-mucin phase and ensures the preservation of homeostasis of the ocular surface. Meibum is a lipid-rich secret produced by fully differentiated meibocytes. Impaired insulin secretion, insulin resistance, absolute insulin deficiency, as well as hyperglycemia, potentiate the development of oxidative stress and a cascade of metabolic changes, leading to a change in the anatomical and functional state of the meibomian glands, which affects the qualitative and quantitative secretion. Cytological abnormalities, as well as the structure of the excretory ducts of the meibomian glands in patients with long-term diabetes mellitus, were established using the method of laser scanning microscopy. Using the method of mass spectrometry, it is possible to determine the patterns of changes in the chemical composition of meibum in patients with diabetes mellitus. The data obtained can become one of the criteria for predicting the course, reflect the degree of compensation and / or progression of diabetes mellitus.